Increased Productivity of Carrot (Daucus carota L) Plants by Giving Goat Manure and SIPLO Induction Time (Local Potential Intensification System) - Juwita Mayang Sari; Istirochah Pujiwati; Sugiarto Sugiarto (AGRONISMA, 2021)
ABSTRACTCarrot production according to data from the Central Statistics Agency in 2020 is 80.39 tons/ha, while the productivity of carrots in Batu is an average of 11.13 tons/ha. The purpose of this study was to increase the productivity of carrot plants by applying goat manure and SIPLO induction duration. The method used was a factorial randomized block design (RAK) with controls. The first factor is the dose of goat manure (P1) ; 7.5 tons/ha, (P2); 10 tons/ha, (P3) ; 12.5 tons/ha. The second factor is the duration of SIPLO induction (I1) ; 45 minutes, (I2) ; 60 minutes, (I3) ; 75 minutes. Data analysis used analysis of variance and further test BNJ, Dunnet test 5%. The treatment dose of 10 goat manure and 60 minutes of SIPLO induction had a significant effect on increasing the number of leaves at 44 days after planting (21.33 strands). The application of goat manure 10 tons/ha and SIPLO induction duration of 75 minutes was able to increase the fresh weight of tubers planted, the weight of tons/ha and the harvest index. fresh weight of tubers planted reached 44.86% when compared to those that were not given an increase. The increase in weight tons/ha reached 44.87% when compared to those who were not treated.